Dosis de compost de rastrojos de nabo en las características agronómicas y rendimiento de Brassica sinensis L., col china, en la Región Loreto, 2023 - Goycochea Fajardo, Daniela del Pilar (2024)
The study was conducted in a type of sandy loam soil, located near the town of Zungarococha Km 3 on the Quisto cocha – Llanchama road, where different doses of turnip compost were used in the cultivation of Chinese cabbage in order to determine its influence on the agronomic characteristics and yield of the plants and determine the most effective dose. The statistical design used for this purpose was the DBCA given to the physical and chemical characteristics of the soil; to determine the statistical significance of the treatments studied with doses of 30, 40, 50 and 60 t of compost/ha; To this end, Tuckey's comparison test was used, concluding in turnip compost influenced the agronomic characteristics and yield of Chinese cabbage; the dose of 60 t of compost/ha (T4) gave the main results in agronomic characteristics and yield with the exception of root length; T4 with doses of 60 t of compost/ha presented the best plant weight with 815 g and plant weight/ha with 54,000.27 kg; Q4 presented the best productivity in Chinese cabbage with a profitability of S/.33,705.27.